Public Expenditure and Consumption Volatility - Herrera, Santiago; Vincent, Bruno (World Bank, Washington, DC, 2012)
Recent estimates of the welfare cost of consumption volatility find that it is significant in developing nations, where it may reach an equivalent of reducing consumption by 10 percent per year. Hence, examining the determinants of consumption volatility is of utmost relevance. Based on cross-country data for the period 1960-2005, the paper explains consumption volatility using three sets of variables: one refers to the volatility of income and the persistence of income shocks; the second set of variables refers to policy volatility, considering the volatility of public spending and the size of government; while the third set captures the ability of agents to smooth shocks, and includes the depth of the domestic financial markets as well as the degree of integration to international capital markets. To allow for potential endogenous regressors, in particular the volatility of fiscal policy and the size of government, the system is estimated using the instrumental variables method. The results indicate that, besides income volatility, the variables with the largest and most robust impact on consumption volatility are government size and the volatility of public spending. Results also show that deeper and more stable domestic financial markets reduce the volatility of consumption, and that more integrated financial markets to the international capital markets are associated with lower volatility of consumption.